Konteks Histori Yang Menyebabkan Lahirnya Rumusan Sila Pertama Pancasila - Dewi Romantika Tinambunan; Yakobus Ndona (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Pancasila, as the basis of the Republic of Indonesia, has an interesting historical background to research. This research aims to analyze the reasons behind the birth of the formulation of the first principle of Pancasila